Metabolic Stress Responses in Labeo rohita Subjected to Di (2-ethylhexyl) Phthalate (DEHP), Dibutyl Phthalate (DBP), and Diethyl Phthalate (DEP) - Gayathri, D.; Shakila, L. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
This study investigates the stress response of glucose and cholesterol levels in Labeo rohita (Rohu) upon exposure to three widely used phthalates: Di(2-ethylhexyl) phthalate (DEHP), Dibutyl phthalate (DBP), and Diethyl phthalate (DEP). Phthalates, recognized for their endocrine-disrupting properties, are prevalent environmental contaminants. Specimens of Labeo rohita were subjected to environmentally relevant concentrations of DEHP, DBP, and DEP over a controlled period. Blood samples were collected periodically to measure fluctuations in glucose and cholesterol levels, serving as biomarkers of metabolic stress. The results indicate significant alterations in both glucose and cholesterol concentrations, with each phthalate demonstrating a distinct impact on these metabolic parameters. DEHP and DBP elicited more pronounced disruptions compared to DEP, underscoring their higher toxicity. These findings highlight the differential metabolic responses of Labeo rohita to various phthalates and underscore the ecological risks associated with phthalate contamination. The study advocates for stricter regulatory measures to mitigate phthalate pollution and protect aquatic ecosystems. This research enhances our understanding of the biochemical pathways affected by phthalate exposure and lays the groundwork for future investigations into the mechanisms underlying phthalate-induced stress in fish.